Managerial Share Ownership, Audit Committee, and CSR Disclosure Impact to Enterprise Value - Hadiati, Mulyana Chandra; Z, Annisa Hakim (Jurnal ASET (Akuntansi Riset), 2025)
The purpose of this research is to analyse the effect of managerial ownership and the audit committee on the disclosure of corporate social responsibility (CSR) and how it subsequently affects firm value. This study employs multiple regression and path analysis as its analytical methods, utilizing SPSS version 25 for the statistical processing. Based on the linear regression model and hypothesis testing conducted on 46 companies, the findings indicate a significant correlation between managerial ownership and the audit committee with CSR disclosure. The simple linear regression test between CSR and company value does not confirm a significant impact of CSR disclosure on firm value. Similarly, no substantial evidence was found to support the influence of managerial ownership and the audit committee on enterprise value. However, the findings do validate a strong causal relationship between managerial ownership, the audit committee, and CSR disclosure. But the statistical analysis on 46 mining companies failed to prove a significant impact of CSR Disclosure on Enterprise Value. Novelty – this research ran on data of 46 mining companies listed on IDX year 2021 – 2023 and involving four variables that each variable simultaneously influences the other.